2018
DOI: 10.1186/s40834-018-0080-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of glucose intolerance and metabolic syndrome within one year following delivery of a pregnancy complicated by gestational diabetes

Abstract: BackgroundWomen with a history of gestational diabetes (GDM) are at risk for development of both overt Type 2 diabetes (T2DM) and cardiovascular disease (CVD) at higher rates and at earlier ages than control women. Current guidelines recommend longitudinal testing of glucose tolerance for women with prior GDM, but no formal assessments of cardiovascular disease are suggested. This study estimated the prevalence of metabolic syndrome in women with GDM in recent pregnancy who were followed for at least 1 year po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…However, the females in this study with a GDM history reported their T2DM diagnosis was made only after seeking care for symptoms, often up to 2-year postpartum. These accounts, and those in the literature, support current standards for ongoing glucose monitoring for women with a GDM history, illustrate the importance of taking the aforementioned risk factors into account in patient care, and provide a basis for extending regular glucose monitoring beyond 1-year postpartum (ADA, 2020b;Rayanagoudar et al, 2016;Sodhi & Nelson, 2018). It may also be well advised that providers and educators present GDM as a risk factor for developing T2DM to avoid any misinterpretation about the importance of making the recommended lifestyle changes.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…However, the females in this study with a GDM history reported their T2DM diagnosis was made only after seeking care for symptoms, often up to 2-year postpartum. These accounts, and those in the literature, support current standards for ongoing glucose monitoring for women with a GDM history, illustrate the importance of taking the aforementioned risk factors into account in patient care, and provide a basis for extending regular glucose monitoring beyond 1-year postpartum (ADA, 2020b;Rayanagoudar et al, 2016;Sodhi & Nelson, 2018). It may also be well advised that providers and educators present GDM as a risk factor for developing T2DM to avoid any misinterpretation about the importance of making the recommended lifestyle changes.…”
Section: Discussionmentioning
confidence: 61%
“…Although Rayanagoudar and colleagues' (2016) were unable to provide progression rates for specific ethnic subgroups, they concluded that a history of GDM, family history of diabetes, non-White ethnicity, and excess weight contributed to increased risk of T2DM results that are also supported by others (Sodhi & Nelson, 2018). In Sodhi and Nelson's (2018) retrospective chart review of primarily Latinx women, over 25.5% of those with recent GDM experienced worsening glucose tolerance within 1-year postpartum. However, the females in this study with a GDM history reported their T2DM diagnosis was made only after seeking care for symptoms, often up to 2-year postpartum.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[ 3 ] In the long term, GDM increases the risk of T2DM and metabolic syndrome in later years. [ 23 24 ] Shriraam et al 2013[ 25 ] found low awareness of GDM among antenatal women from rural area in South India. Knowledge on risk factors of GDM and subsequent risk of developing T2DM was also low among the antenatal women.…”
Section: Discussionmentioning
confidence: 99%